Modern approaches to study of Rickettsiales - N. V. Rudakov; S. N. Shpynov; I. E. Samoylenko; L. V. Kumpan; T. A. Reshetnikova (Бюллетень сибирской медицины)
We describe wide distribution and considerable biological and genetical heterogeneity of Rickettsiales in Russia and Ka- zakhstan. R. sibirica subsp. sibirica, R. sibirica subsp. BJ-90, R. slovaca, R. helvetica, R.heilongjiangensis, R.aeschlimannii, R.tarasevichiae were detected in Siberia and Russian Far East. Our results show circulation of R.massiliae genotypes (R.sp.RpA4, R.sp.DnS14, R.sp.DnS28) in Dermacentor ticks, Ehrlichia muris, Anaplasma phagocytophila, «Schotti variant» — in I. persulcatus, H. concinna — in A. bovis. Role of new genotypes of .1Proteobacteria in infectology is in need of further specification.